Posturographic limits of stability can predict the increased risk of falls in elderly patients with instability? - Faraldo-García, Ana; Santos-Pérez, Sofía; Rossi-Izquierdo, Marcos; Lirola-Delgado, Antonio; Vaamonde-Sánchez-Andrade, Isabel; del-Río-Valeiras, María; Soto-Varela, Andrés (Acta oto-laryngologica, 2016)
Conclusions: There was a difference in average score of the sensory organization test (SOT) of the case group (elderly instability) compared to the control group (healthy subjects). Cases had worse scores on the limits of stability (LOS) than controls, but were only able to confirm statistically significant differences in the movement velocity. Objective: To study the LOS of elderly patients with instability vs healthy subjects of the same age to try to explain the increased risk of falls in elderly patients with instability. Methods: Fifty individuals ≥65 years, 30 cases (at least one of the next inclusion criteria: ≥1 fall in the last 12 months, >15 s or some support in the timed up and go test, composite <68 in SOT, ≥1 fall during production of the SOT) compared to 20 controls. Postural study: SOT and LOS, Smart Equitest Neurocom ® platform. Statistical analysis: t-Student test (p < 0.05). Result: Mean value of overall balance: patients with instability =56% vs controls =77.1% (p < 0.001). Movement velocity: cases =2243°/s vs controls =2860°/s (p = 0.029). The reaction time (cases =1217 s vs controls =1.077 s), excursion (56.95% vs 59.35%) and directional control (56.95% vs 59.35%) differences were not statistically significant.